2021
DOI: 10.19245/25.05.pij.6.1.3
|View full text |Cite
|
Sign up to set email alerts
|

https://www.puntoorginternationaljournal.org/index.php/PIJ/article/view/97

Abstract: https://www.puntoorginternationaljournal.org/index.php/PIJ/article/view/97

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…However, gender stereotypes should be more present in crowdfunding than in other financial markets. "When there is limited access to information, individuals are more prone to rely on underlying stereotypes (Tosi and Einbender, 1985), and crowdfunding markets undoubtedly represent this situation" (Battaglia et al, 2021). Yet, as Wesemann and Wincent (2021) recently stated, crowdfunding challenges many causes of gender discrimination.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, gender stereotypes should be more present in crowdfunding than in other financial markets. "When there is limited access to information, individuals are more prone to rely on underlying stereotypes (Tosi and Einbender, 1985), and crowdfunding markets undoubtedly represent this situation" (Battaglia et al, 2021). Yet, as Wesemann and Wincent (2021) recently stated, crowdfunding challenges many causes of gender discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Cicchiello et al (2021, p. 930) suggested that equity crowdfunding campaigns should be based on gender equality on the firms' boards. Battaglia et al (2021) found that companies founded by women are more successful in receiving financial backing, involving more investors, and achieving their fundraising goals easier than their male counterparts. The female advantage is more substantial in countries where women are disadvantaged and far from equal opportunities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation